The 100 Most-Cited Articles in Liposuction: A Bibliometric Analysis. Issue 6 (28th December 2021) - Reddy, Rohin K.; Dutt, Atul; Charles, Walton N.; Hoyos, Alfredo; Khajuria, Ankur
Abstract : Supplemental digital content is available in the text. Abstract : Background: Liposuction is one of the most common cosmetic surgical procedures performed worldwide. Despite previous citation analyses in plastic surgery, the most-cited works in liposuction have not yet been qualitatively or quantitatively appraised. We hypothesized that use of validated outcome measures and levels of evidence would be low among these articles. Thus, we performed a bibliometric analysis aiming to comprehensively review the most-cited liposuction literature, evaluating characteristics and quality of the top 100 articles. Methods: The 100 most-cited articles in liposuction were identified on Web of Science, across all available journals and years (1950–2020). Study details, including the citation count, main subject, and outcome measures, were extracted from each article by 2 independent reviewers. The level of evidence of each study was also assessed. Results: The 100 most-cited articles in liposuction were cited by a total of 4809 articles. Citations per article ranged from 602 to 45 (mean, 92). Most articles were level of evidence 4 (n = 33) or 5 (n = 35), representative of the large number of case series, expert-opinion articles, and narrative reviews. Ten articles achieved level of evidence 3, 22 articles achieved level of evidence 2, and none reached level 1. The main subject was operative technique in 63 articles, followed by outcomes in 32 articles. Five articles assessed the metabolic effects of liposuction. Only 1 article used a validated objective cosmetic outcome measure, and none used validated patient-reported outcome measures. Conclusions: This analysis provides an overview of the top cited liposuction literature. Overall, level of evidence was low, and no articles achieved the highest level of evidence. Improving the quality of literature requires prioritization of better-designed studies and incorporation of validated outcome measures, which will increase patient satisfaction and ensure provision of excellent, reproducible clinical care.